Efektivitas hyaluronic acid 0,1% terhadap penyembuhan luka trauma akibat piranti ortodontik cekat Effectivity of 0.1% hyaluronic acid toward to healing of trauma injury due to fixed orthodontics - Hanna Silvia Debora; Nada Ismah; Benny Mulyono Soegiharto (DiscoverSys Inc., 2012)
Treatment with a fixed orthodontic aims to improve malocclusion and enhance the aesthetic. Traumatic injury to themucosa of the mouth is one of the risks that often occur and can be addressed among others by using mouthwashthat contains hyaluronic acid. This study aimed to determine the effectiveness of 0.1% hyaluronic acid on woundhealing caused by trauma of fixed rthodontic appliance in terms of size wound, redness and pain. Twenty twopatients who had a traumatic injury caused by fixed appliance on buccal or labial mucosa were divided into 2groups: K1, was instructed to rinse 10 ml solution containing 0.1% hyaluronic acid for 2 minutes after brushingteeth, 2 times a day for 4 days; K2, used the K1’s instruction but using a placebo solution. Examination of size areused caliper and reddish wounds are used index measuring wound redness performed before and after treatment,and pain measurement used questionnaires. Based on the statistical analysis of t-test, the percentage of size changes and redness traumatic injury were more significant in K1 than in K2 (p<0.05). While the pain of traumatic changesin K1 than in K2 were not significant (p>0.05). The use of mouthwash containing 0.1% hyaluronic acid wasconcluded proved effective to accelerate the wound healing process, but does not prove effective reducing paincaused by traumatic injury due to fixed orthodontic appliance.